2014
DOI: 10.1116/1.4866378
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plasma-enhanced atomic layer deposition of Al2O3 using dimethylaluminum isopropoxide

Abstract: In this research, Al2O3 films were grown by remote plasma-enhanced atomic layer deposition using a nonpyrophoric precursor, dimethylaluminum isopropoxide (DMAI), and oxygen plasma. After optimization, the growth rate was determined to be ∼1.5 Å/cycle within a growth window of 25–220 °C; the higher growth rate than reported for thermal atomic layer deposition was ascribed to the higher reactivity of the plasma species compared with H2O and the adsorption of active oxygen at the surface, which was residual from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…A previous study from our group reported the band gap of PEALD Al 2 O 3 as 6.7 6 0.1 eV, which was determined from XPS O 1s energy loss spectroscopy. 12 The result is consistent with other results. 33,34 Using 6.7 eV as the band gap of the Al 2 O 3 films, the respective CBO was $1.2 and 1.4 eV for Al 2 O 3 on Ga-and N-face GaN, respectively.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…A previous study from our group reported the band gap of PEALD Al 2 O 3 as 6.7 6 0.1 eV, which was determined from XPS O 1s energy loss spectroscopy. 12 The result is consistent with other results. 33,34 Using 6.7 eV as the band gap of the Al 2 O 3 films, the respective CBO was $1.2 and 1.4 eV for Al 2 O 3 on Ga-and N-face GaN, respectively.…”
Section: Resultssupporting
confidence: 83%
“…The PEALD system has been discussed in detail elsewhere. 12 The precursors used for HfO 2 48,90, and 33 C to provide sufficient vapor pressure for PEALD deposition. The delivery line temperatures were maintained at $20 C higher than that of the specific bubbler to prevent precursor condensation.…”
Section: B Peald Dielectric Growth and Post Deposition Annealingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimethylaluminum isopropoxide (DMAI) was proposed by a few groups as an alternative CVD precursor to produce alumina films using evaporation or bubbling systems . DMAI was also tested for atomic layer deposition (ALD) of alumina in a few instances . This molecule consists of an Al atom linked to two methyl and one isopropyl groups, and has an intermediate structure between ATI and TMA.…”
Section: Introductionmentioning
confidence: 99%
“…3, was used to estimate the onset of the bulk plasmon relative to the center of the 1s peak. Previous studies have demonstrated that the bandgap of a material can be deduced by determining the position of the bulk plasmon onset relative to the core level peak [34,35]. This analysis indicated a bandgap of 6.2±0.2 eV.…”
Section: Accepted Manuscriptmentioning
confidence: 95%